2013
DOI: 10.1249/mss.0b013e31829efcf7
|View full text |Cite
|
Sign up to set email alerts
|

Forefoot Strikers Exhibit Lower Running-Induced Knee Loading than Rearfoot Strikers

Abstract: To our knowledge, this is the first study that shows differences in patellofemoral loading and knee frontal plane moment between FFS and RFS. FFS exhibit both lower patellofemoral stress and knee frontal plane moment than RFS, which may reduce the risk of running-related knee injuries. On the other hand, parallel increase in ankle plantarflexor and Achilles tendon loading may increase risk for ankle and foot injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
215
8
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(263 citation statements)
references
References 32 publications
23
215
8
1
Order By: Relevance
“…Reduced work at the knee joint might have resulted from the increased stride rate and strike index that occurred when using minimalist shoes. Researchers 29,30 have demonstrated that running with an increased stride rate or an FF decreases knee-joint contact forces. Therefore, minimalist shoes could be used to reduce the risk of injury at the knee, which is one of the most commonly injured joints in running, 9 by facilitating an MF and increased stride rate.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced work at the knee joint might have resulted from the increased stride rate and strike index that occurred when using minimalist shoes. Researchers 29,30 have demonstrated that running with an increased stride rate or an FF decreases knee-joint contact forces. Therefore, minimalist shoes could be used to reduce the risk of injury at the knee, which is one of the most commonly injured joints in running, 9 by facilitating an MF and increased stride rate.…”
Section: Discussionmentioning
confidence: 99%
“…Kulmala et al 22 reported that a forefoot strike pattern resulted in a 14.6% reduction in peak PFJ stress compared to a rearfoot strike pattern. Bonacci et al 6 reported that barefoot running led to a 12% reduction in peak PFJ stress compared to shod running.…”
Section: Discussion Tmentioning
confidence: 99%
“…In addition, an association between running fatigue and magnitude of plantar pressure was suggested after short races with 400 m distance 9 . The increased loading in forefoot of 10 km runners may also suggest attention for training, as this pattern of loading can influence the development of patellofemoral pain syndrome 16 , which depends on the running technique 17 , and is a risk factor for ankle injuries such as ankle sprains 18 . Considering a regular involvement in running training, the persistence of changes after competition (up to 24 h after a prolonged running 19 ) suggest further attention to the foot health among athletes and coaches.…”
Section: Discussionmentioning
confidence: 99%